Primary Hepatic Leiomyosarcoma Report of a rare case with review of literature - Rao, B. Vishal; Arya, Sahithi Shilpa; Murthy, S. Sudha; Prasad, Yalavarthi (Indian Journal of Case Reports, 2016)
Primary hepatic leiomyosarcoma is an extremely rare tumor with a dismal prognosis and difficulty in diagnosis. We present a 36-year-old female who presented with complaints of pain in right hypochondrium and epigastric region. Real-time ultrasonography revealed an enlarged liver with multiple hypoechoic lesions of varying sizes in both the lobes of the liver. USG guided core biopsy from the lesion showed an infiltrating malignant spindle cell neoplasm positive for smooth muscle actin and caldesmon-H confirming the diagnosis of leiomyosarcoma. It is vital to diagnose these lesions even on limited biopsies as early diagnosis can reduce hospital and operative morbidity and mortality rates in the patients.